2006
DOI: 10.1158/0008-5472.can-06-1950
|View full text |Cite
|
Sign up to set email alerts
|

SLC5A8 Triggers Tumor Cell Apoptosis through Pyruvate-Dependent Inhibition of Histone Deacetylases

Abstract: Tumor cells up-regulate glycolysis but convert pyruvate into lactate instead of oxidizing it. Here, we show that pyruvate, but not lactate, is an inhibitor of histone deacetylases (HDAC) and an inducer of apoptosis in tumor cells and that SLC5A8, a Na + /monocarboxylate cotransporter, is obligatory for this process. We found that SLC5A8 is expressed in nontransformed breast epithelial cell lines but silenced by DNA methylation in tumor cell lines. The down-regulation of the gene is also evident in primary brea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 20 publications
7
130
0
1
Order By: Relevance
“…Neoplastic cells accomplish the consumption of the surplus pyruvate generated by glycolysis, which is not fed into the TCA cycle, also by conversion into lactate by lactate dehydrogenase (LDH)-A (Shim et al, 1997) and by fueling it into lipid biosynthesis . Removal of this excess of pyruvate molecules is crucial to avoid pyruvate-induced apoptosis (Thangaraju et al, 2006). In addition, overexpression of the monocarboxylate transporter (MCT4) gene allows augmented extrusion of lactate along with protons to the extracellular milieu (Gallagher et al, 2007).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…Neoplastic cells accomplish the consumption of the surplus pyruvate generated by glycolysis, which is not fed into the TCA cycle, also by conversion into lactate by lactate dehydrogenase (LDH)-A (Shim et al, 1997) and by fueling it into lipid biosynthesis . Removal of this excess of pyruvate molecules is crucial to avoid pyruvate-induced apoptosis (Thangaraju et al, 2006). In addition, overexpression of the monocarboxylate transporter (MCT4) gene allows augmented extrusion of lactate along with protons to the extracellular milieu (Gallagher et al, 2007).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…The Na ϩ -coupled monocarboxylate transporter SLC5A8 (human ortholog is in uppercase letters, and rodent ortholog is in lowercase letters) is necessary for the entry of butyrate into colon cells for subsequent inhibition of HDACs (14,15). Recently we have shown that propionate, another short-chain fatty acid produced in the colon by bacterial fermentation, is also an inhibitor of HDACs (16). SLC5A8 has been shown to function as a tumor suppressor in the colon (17) and other tissues (13,18,19); the ability of this transporter to mediate the Na ϩ -coupled entry of HDAC inhibitors (butyrate, propionate, and pyruvate) into cells underlies the tumor-suppressive function of this transporter (15,16).…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…Recently we have shown that propionate, another short-chain fatty acid produced in the colon by bacterial fermentation, is also an inhibitor of HDACs (16). SLC5A8 has been shown to function as a tumor suppressor in the colon (17) and other tissues (13,18,19); the ability of this transporter to mediate the Na ϩ -coupled entry of HDAC inhibitors (butyrate, propionate, and pyruvate) into cells underlies the tumor-suppressive function of this transporter (15,16). While SLC5A8 is necessary for the intracellular actions of butyrate, butyrate also elicits biologic effects on colon cells extracellularly by serving as an agonist for the cell surface G-protein-coupled receptor GPR109A, but without involving HDAC inhibition (20).…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…We selected the breast cancer cell line MCF7 for this purpose. We have shown that breast cancer is also associated with the silencing of SLC5A8 and that MCF7 cell line, being a malignant cell, does not express the transporter (32). Therefore, a MCF7 cell line engineered to express SLC5A8 stably would be ideal for the screening.…”
Section: Slc5a8 As a Tumor Suppressor In Non-colonic Tissues: Mechanimentioning
confidence: 99%